Hepatic Alteration due to Formaldehyde Exposure on Wistar Rats (Rattus norvegicus) - Makbul, Hidayat; Wedayani, Anak Agung Ayu Niti; Punagi, Abdul Qadar; Pieter, Nova Audrey Luetta; Cangara, Muhammad Husni; Lestarini, Ima Arum; Restuningdyah, Novia Andansari Putri (Jurnal Biologi Tropis, 2024)
Formaldehyde is a hazardous chemical substance that can be found commonly in the environment which has various effects on cellular functions and could induce the cellular oxidative stress. Oxidative stress has a direct impact on the hepatic condition and could induce the activation of inflammatory mediators, lipid peroxidation, proteosomal degradation, and mitochondrial dysfunction resulting in hepatocyte injury that could be marked by hepatic enzyme elevation and hepatic weight alterations. This research was conducted using 16 Wistar rats (Rattus norvegicus), divided into 4 groups each containing 4 Wistar rats. The first group was the control group, while the other groups were exposed to formaldehyde 10% by inhalation at doses of 20, 30, and 40 ppm formaldehyde persistently for 6 hours daily for about 16 weeks. The result of this study reveals that formaldehyde induction has a significant impact on hepatic weight elevations (p=0.007) and ALT enzyme elevations (p=0.000) in the treatment groups compared with the control group. Collectively, our results provide valuable information on the hazardous effects of formaldehyde inhalation, especially on the liver.